A time course study of high on treatment platelet reactivity in acute coronary syndrome male patients on dual antiplatelet therapy. Issue 3 (September 2015) - Fabbri, Alessia; Marcucci, Rossella; Gori, Anna Maria; Giusti, Betti; Paniccia, Rita; Balzi, Daniela; Barchielli, Alessandro; Valente, Serafina; Giglioli, Cristina; Abbate, Rosanna; Gensini, Gian Franco
Abstract Introduction Limited data are available on the natural history of high on treatment platelet reactivity (HPR) by arachidonic acid and ADP - markers of unfavorable prognosis in acute coronary syndrome patients -. Material and methods In a cohort of acute coronary syndrome male patients (n = 101), we evaluated the time-course of HPR by ADP (platelet aggregation by 10 μM ADP ≥ 70%) and arachidonic acid (platelet aggregation by 1 mmol arachidonic acid ≥ 20%) measuring platelet function in the acute phase (T0), at 6 months (T1) and 1 year (T2). Results We identified persistent (HPR at T0, T1 and T2), acute non persistent (HPR only at T0), and late (HPR only at T1 or T2). Patients with persistent HPR by ADP were more frequently with higher values of BMI. Patients carrying CYP2C19*2 variant were more prevalent in the group of persistent HPR (33%). Significant higher values of immature platelet fraction and high immature platelet fraction at 6 and 12 months and mean platelet volume were present in patients with late HPR. Immature platelet fraction was the only variable significantly associated with late HPR by ADP at multivariate analysis (OR = 1.6 (1.08-2.3), p = 0.016). Patients with persistent HPR by arachidonic acid were more frequently diabetics. Immature platelet fraction at 6 months and high immature platelet fraction at 6 and 12 months were the parameters associated with late HPR by AA (OR = 1.4 (1.0-1.9), p = 0.036; OR = 1.5 (1.08-2.4), p = 0.05; OR = 4.9 (1.3-18.8), p = 0.018, respectively). Conclusions About 25% of 101 patients has persistent HPR; they are more frequently diabetics, overweight or carriers of CYP2C19*2. The occurrence of an inflammatory state, indicated by the increase of immature platelet fraction, is associated with the occurrence of late HPR.